Impingement and entrainment of fishes at the Dairyland Power Cooperative Alma, Wisconsin power plants - Goeman, Timothy J. (My University, 1981)
The objective of this two-year study was to document the occurrence of impingement and entrainment of fishes at two of Dairyland Power Cooperative's cooling water intakes on Navigation Pool 5 of the Upper Mississippi River during 1979 and 1980. Impingement at the 208 MW Alma units 1-5 intake during 1979-1980 consisted of 33 species from 13 families. During 1979 sampling, 586 fishes were impinged. During 1980 sampling at Alma 1-5, 1165 fishes were impinged. The weekly 24-hour impingement samples were used to project the two-year annual mean impingement of 10,735 fishes. Gizzard shad(40.0%) and black crappie (23.1%) were the most commonly impinged species during the study. The annual entrainment of larval fishes at Alma 1-5 was estimated at 125,000 during 1980. Impingement studies at the 350 MW J. P. Madgett Station intake began with its operation in November 1979 and continued through 1980. IMring sampling, 29 species from 9 families were impinged, including 3 crystal darters (ammocrypta asprella), which had not been previously recorded in Pool 5. A total of 3980 impinged fishes were sampled during the 11 months of the study. The weekly 24-hour impingement samples were used to project the total impingement of 33,791 fishes for the J. P. Madgett intake during the study period. Gizzard shad comprised 63.8% of the total numbers and 14.0% were freshwater drum. Annual variations in impingement were attributed to varying densities of juvenile fishes in the vicinity of the intakes. This was likely influenced primarily by spawning success. Over 90% of all fishes impinged were juveniles. A fish mortality study at the J. P. Madgett intake showed that survival of impinged fishes was species-specific. Survival of all fishes impinged during sampling was 16.6%. The efficiency of removal of fishes from the fish trays on the vertical traveling screens by the low pressure spray jets was calculated to be approximately 96%. The combined estimated total biomass of fishes impinged at both intakes during 1980 represented approximately 0.4% by weight of the total annual harvest of Pool 5. Both intake structures were located in areas that were not conducive to high fish densities. Differences between impingement rates at the two intake structures was likely due, in part, to the larger surface area and greater intake volume at the J. P. Madgett intake.
Keywords: Dairyland Power Cooperative. Alma Station -- Environmental aspects; Power-plants -- Environmental aspects -- Wisconsin -- Alma; Dairyland Power Cooperative. J.P. Madgett Station -- Environmental aspects